Evaluation of the Western blotting method for the diagnosis of congenital toxoplasmosis - Jaqueline Dario Capobiango; Thaís Cabral Monica; Fernanda Pinto Ferreira; Regina Mitsuka-Breganó; Italmar Teodorico Navarro; João Luis Garcia; Edna Maria Vissoci Reiche (Jornal de Pediatria, 2016)
Objective: To evaluate the Western blotting method for the detection of IgG anti-Toxoplasma gondii (T. gondii) (IgG-WB) in the serum of children with suspected congenital toxoplasmosis. Methods: We accompanied 47 mothers with acquired toxoplasmosis in pregnancy and their children, between June of 2011 and June of 2014. The IgG-WB was done in house and the test was considered positive if the child had antibodies that recognized at least one band on IgG blots different from the mother's or with greater intensity than the corresponding maternal band, during the first three months of life. Results: 15 children (15.1%) met the criteria for congenital toxoplasmosis and 32 (32.3%) had the diagnosis excluded. The symptoms were observed in 12 (80.0%) children and the most frequent were cerebral calcification in 9 (60.0%), chorioretinitis in 8 (53.3%), and hydrocephalus in 4 (26.6%). IgM antibodies anti-T. gondii detected by chemiluminescence (CL) were found in 6 (40.0%) children and the polymerase chain reaction (PCR) for detection of T. gondii DNA was positive in 5 of 7 performed (71.4%). The sensitivity of IgG-WB was of 60.0% [95% confidence interval (CI) 32.3–83.7%] and specificity 43.7% (95% CI 26.7–62.3%). The sensitivity of IgG-WB increased to 76.0 and 89.1% when associated to the research of IgM anti-T. gondii or PCR, respectively. Conclusions: The IgG-WB showed greater sensitivity than the detection of IgM anti-T. gondii; therefore, it can be used for the diagnosis of congenital toxoplasmosis in association with other congenital infection markers. Resumo: Objetivo: Avaliar o método Western Blotting para detecc¸ão de IgG anti-Toxoplasma gondii(T. gondii) (IgG-WB) no soro de crianc¸as com suspeita de toxoplasmose congênita Métodos: Acompanhamos 47 mães com toxoplasmose adquirida na gravidez e seus filhos, entrejunho de 2011 e junho de 2014. O IgG-WB foi feito internamente e o teste foi consideradopositivo quando a crianc¸a apresentava anticorpos que reconheciam pelo menos uma bandanas manchas de IgG diferente das bandas da mãe ou com maior intensidade do que a bandamaterna correspondente, durante os primeiros 3 meses de vida Resultados: Atenderam aos critérios para diagnóstico de toxoplasmose congênita 15crianc¸as (15,1%) e 32 (32,3%) tiveram o diagnóstico excluído. Os sintomas foram observados em12 crianc¸as (80%) e os mais frequentes foram calcificac¸ão cerebral em nove (60%), coriorretiniteem oito (53,3%) e hidrocefalia em quatro (26,6%). Os anticorpos IgM anti-T. gondii detectadospor quimiluminescência (QL) foram encontrados em seis crianc¸as (40%) e a reac¸ão em cadeiada polimerase (RCP) para detecc¸ão do DNA de T. gondii foi positiva em cinco de sete reac¸ões(71,4%). A sensibilidade do IgG-WB foi de 60% [intervalo de confianc¸a (IC) de 95%, 32,3 a 83,7%]e a especificidade foi de 43,7% (IC de 95%, 26,7 a 62,3%). A sensibilidade do IgG-WB aumentoupara 76 e 89,1% quando relacionada à pesquisa de IgM anti-T. gondii ou à RCP, respectivamente Conclusões: O IgG-WB mostrou maior sensibilidade do que a detecc¸ão de IgM anti-T. gondii;portanto, pode ser usado para o diagnóstico de toxoplasmose congênita em associac¸ão comoutros marcadores de infecc¸ão congênita. Keywords: Congenital Toxoplasmosis, Western Blotting, Diagnosis, Serology, Palavras-chave: Toxoplasmose Congênita, Western blotting, Diagnóstico, Sorologia